Synthesis and characterization of lithium calcium phosphate ceramics - Kaygili, Omer; Keser, Serhat; Ates, Tankut; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2013)
The crystal structure, thermal, dielectrical, alternating current conductivity and microstructure properties of lithium calcium phosphate ceramics synthesized by the sol gel method were investigated. The average crystallite size, crystallinity, activation energy and enthalpy of crystallization of Ca10Li(PO4)(7) ceramics were determined. The X-ray diffraction (XRD) results indicated that the apatitic structure belonging to HAp was transformed fully to Ca10Li(PO4)(7) phase with the addition of Li. The Avrami exponents of the samples suggest that the crystallization mechanism is based on the surface nucleation and one-dimensional growth. It was found that the alternating current conductivity mechanism of the ceramics is controlled by the hopping motion involving a translational motion with a sudden hopping. The dielectric constant of the samples shows a small increase with increasing amount of Li. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Sol-gel method; Calcium phosphates; Activation energy; Crystal structure